Self‐Cleaning Surfaces Realized by Biologically Sized Magnetic Artificial Cilia. Issue 5 (30th December 2021) - Cui, Zhiwei; Zhang, Shuaizhong; Wang, Ye; Tormey, Laura; Kanies, Olivia S.; Spero, Richard Chasen; Fisher, Jay K.; den Toonder, Jaap M. J.
Abstract: Magnetic artificial cilia (MAC) are small actuators inspired by biological cilia found in nature. In microfluidic chips, MAC can generate flow and remove microparticles, with applications in anti‐fouling. However, the MAC used for anti‐fouling in the current literature has dimensions of several hundred micrometers in length, which limits the application to relatively large length scales. Here, biologically‐sized magnetic artificial cilia (b‐MAC) which are only 45 micrometers long and that are randomly distributed on the surface, are used to remove microparticles. It is shown that microparticles with sizes ranging from 5 to 40 µm can be removed efficiently and the final cleanness ranges from 69% to 100%, with the highest cleanness for the highest actuation frequency applied (40 Hz). The lowest cleanness is obtained for microparticles with a size equal to the average pitch between the b‐MAC. The randomness in cilia distribution appears to have a positive effect on cleanliness, compared with the authors' earlier work using a regular cilia array. The demonstrated self‐cleaning by the b‐MAC constitutes an essential step toward efficient self‐cleaning surfaces for real‐life application in miniaturized microfluidic devices, such as lab‐on‐a‐chip or organ‐on‐a‐chip devices, as well as for preventing fouling of submerged surfaces such as marine sensors. Abstract : The authors use small‐scaled magnetic artificial cilia with a size comparable to biological cilia to remove microparticles efficiently. In this way, they can create a self‐cleaning surface successfully. The artificial cilia can remove microparticles with different sizes. Besides, a high cleanness can be reached not only by changing actuation frequency but also by changing actuation direction.